Engineering Bacillus subtilis for production of 3-hydroxypropanoic acid - Garg, Abhroop; Jers, Carsten; Hwang, Hee Jin; Kalantari, Aida; Ventina, Ildze; Mijakovic, Ivan (Frontiers in Bioengineering and Biotechnology, 2023)
3-Hydroxypropionic acid (3-HP) is a valuable platform chemical that is used as a precursor for several higher value-added chemical products. The chemical synthesis of 3-HP in petroleum oil refineries is a costly process, which also leads to generation of toxic intermediates with environmental effects. This, along with the diminishing global crude oil reserves has led to an increased interest in development of cell factories as a means for the synthesis of various platform chemicals. For more than a decade, concentrated effort has been invested by the scientific community towards developing bio-based approaches for the production of an extensive range of chemicals, such as 3-HP. As an abundant by-product of the biodiesel industry, glycerol is an attractive substrate for the production of 3-HP. We have previously demonstrated that Bacillus subtilis can be engineered to produce 3-HP. In the present study, we optimized the bioprocess conditions and further engineered the B. subtilis 3-HP production strain. Thereby, using glycerol as substrate, we were able to improve 3-HP production in a 1-L bioreactor to a final titer of 22.9 g/L 3-HP.